Effect of pH and Stirring Speed on the γ-Fe2O3 Material Properties Synthesized from Iron Sand by Using Co-Precipitation Method - L Agusu; Amiruddin; M. Nalis; S. Misudo; Y. Fujii; Y. Ishikawa; Alimin (International Journal of Acta Material, 2024)
Research has been conducted to investigate the impact of pH and stirring on the magnetic properties of γ-Fe2O3 nanoparticles derived from iron sand using the co-precipitation method. The objective of this study was to synthesize γ-Fe2O3 nanoparticles and examine how pH and stirring affect their size and properties. The co-precipitation method involved mixing iron sand with HCl as a solvent and NH4OH as a precipitator. The experimental setup included variations in pH, specifically pH 10 and pH 12, as well as stirring speeds of 600 rpm and 700 rpm. The synthesized maghemite nanoparticles were characterized using XRD (X-Ray Diffraction), SEM (Scanning Electron Microscope), and VSM (Vibrating Sample Magnetometer) techniques. XRD analysis revealed that the particle size at 600 rpm under pH 10 was 52.085 nm, whereas at 700 rpm under pH 12 it was 47.821 nm. The VSM characterization results demonstrated a remanent magnetization of 25.5 emu/gr, a coercivity field of -0.01 Tesla, and a saturation magnetization of 52.45 emu/gr. This study confirmed that the maghemite nanoparticles produced exhibited ferromagnetic properties.